TOLERANCE TO UNCERTAINTY IN THE SITUATION OF WAR - Chuyko, Halyna; Chaplak, Yan; Koltunovich, Tetyana (PSYCHOLOGICAL JOURNAL, 2024)
The article is related to the theoretical analysis and generalization of scientific information on the problem of tolerance to uncertainty in psychology and an empirical study of the relationship between a person's tolerance to uncertainty and a sense of satisfaction with life, psychological well-being, and the perception of one's life as existentially meaningful. It is noted that, despite the relatively long history of studying the phenomenon of uncertainty tolerance in science and its potential importance, there is still no scientifically based and agreed interpretation of this phenomenon in psychology, since it can be defined by different scientists as: 1) a personal trait / characteristic / property; 2) a social attitude of an individual, containing cognitive, affective and conative components and/or their combination, or 3) a holistic system of a person's response to a situation of uncertainty. It is stated that the essential reason for the emergence of a situation of uncertainty in a person's life is the lack of information necessary for an adequate understanding of the content and consequences of this situation; while this can be both the result of a real lack of the necessary data, and vice versa, it is emphasized by the excessive amount of information available to a person, which with its content and form of presentation (clip-fragmented) only makes it difficult to find the information necessary to solve the situation or its interpretation. As a result of our research, it was established: a person intolerant to uncertainty, understanding it and evaluating it negatively, can show dissatisfaction with his life; while a person who is tolerant of uncertainty tends to feel psychologically well-off with satisfaction and existential meaningfulness of his own existence. It was concluded that tolerance to uncertainty presupposes a person's ability to calmly / without internal tension relate to the lack of information needed in the situation, to accept the presence of an uncertain situation as a component and permanent content of one's own life; to allow the coexistence of contradictory and inconsistent information without a biased attempt to give preference to one part of it or to oppose it to another; the possibility (but not the obligation) to start actions aimed at solving / overcoming the situation of uncertainty, without being sure of their effectiveness; however, hoping to gain new experience and acquire life wisdom; to accept the existence of the uncertain in its various variants (as unknown (completely or partially), ambiguous (ambivalent or ambiguous), not yet resolved, or not resolved at all). However, neither tolerance nor intolerance of uncertainty is a uniquely positive or negative personality trait.